Enhancing Research, Curriculum Development and Alumni Contributions in Selected Institutions of Higher Technical Education: Development of a Framework with Knowledge Management - Agarwal, Parul D (My University, 2012)
In this globalized network society, there is a paradigm shift in education from teacher centric education to learner centric education. It is very important for organizations to “know what they know” and make maximum use of their knowledge. There are hidden, untapped reservoirs of intelligence that exist in almost every organization. There is a difference in ranking in two universities with identical numbers of faculty, degree programs, expenditures, and enrollment. This difference as Milam (2001) suggests is often intangible value added by effective Knowledge Management (KM). The educational institutions can adhere to business organisations and pursue the implementation of KM for having an edge and serving the stakeholders in a better way. The present study endeavors to develop a knowledge management framework for enhancing Research, Curriculum development and Alumni contributions in the selected Institutions of Higher Technical Education (IHTE) in India. Being the power house of knowledge in our society, IHTE have immense knowledge and research plays an important role. The accurate and up to date knowledge about earlier and ongoing research and other administrative related information can be acquired and stored systematically with the implementation of KM in IHTE. One of the main aims of any institution of Higher Technical Education (IHTE) is to impart knowledge to the students in the most effective way, meet the needs of the students more efficiently and improve educational outcomes for the students. To remain ahead of competition, even well-established IHTE have to respond to the challenge by offering learners a dynamic and industry oriented curriculum. To achieve this objective, there is a need to facilitate academia with knowledge management (KM) based platform which can help them design innovative, industry oriented, and state-of-art curriculum. Alumni play an important role for all educational institutions. Their experience can be exploited by having their suggestions and feedback regarding Research, Curriculum Development, career development and placement services. Their valuable feedback needs to be acquired, stored and retrieved efficiently using KM. As Research, Curriculum Development and Alumni contributions are the three important aspects of any educational institution, the current study has been undertaken to design a KM framework based on these three aspects. The objectives of the present study are: • To understand and explore the application of KM in Research, Curriculum Development and Alumni Contributions in IHTE. • To identify and establish the possible linkages amongst Research, Curriculum Development and Alumni Contributions. • To propose a framework for implementing KM in Higher Educational Institutions to reap the benefits of KM in the above mentioned areas. The present study uses a survey method to collect data on these three aspects viz. Research, Curriculum Development and Alumni Contributions from IHTE. The designations of the targeted respondents in the IHTE were categorized into two groups. The first group consists of management, senior academia that is, Professors, Associate Professors who are also dealing with managerial work and also “thinkers” are addressed as group A. The second group consists of Assistant Professors, Lecturers and Research Scholars who will be using and also contributing to the KM system and also the “doers”, are addressed as group B. The survey instrument investigates the features which are obtained from the literature and personal observations or interviews for the inclusion in the knowledge management framework for the institutions of higher technical educational (IHTE). The study also tries to identify the perceived benefits of KM implementation in higher technical education if proposed KM framework is put into practice. The particular stakeholder analysis helped to analyses the features to be included in KM framework. The designed KM framework covers KM enablers, KM processes, KM aspects of IHTE and perceived benefits of KM. The suggested framework will help in improving the quality of Research and Curriculum Development and will also help to incorporate Alumni feedback. Thus the competitiveness of IHTE can be enhanced by adopting the suggested framework. Keywords: Institutions of Higher Technical Education, Knowledge Management, Research, Curriculum Development, Alumni Contributions
Keywords: Knowledge management; Knowledge sharing; Knowledge Framework; Curriculum Development